Risk factors and outcomes after interruption of sedation in subarachnoid hemorrhage (ROUTINE-SAH)—a retrospective cohort study - Schmidbauer, Moritz L.; Läufer, Sebastian; Maskos, Andreas; Dimitriadis, Konstantinos (Frontiers in Neurology, 2024)
Introduction Aneurysmal subarachnoid hemorrhage (aSAH) often necessitates prolonged sedation to manage elevated intracranial pressure (ICP) and prevent secondary brain injury. Optimal timing and biomarkers for predicting adverse events (AEs) during interruption of sedation (IS) after prolonged sedation are not well established. To guide sedation management in aSAH, we aimed to explore the frequency, risk factors and outcomes of IS in aSAH. Methods In a retrospective cohort study, a total of 148 patients with aSAH from January 2015 to April 2020 were screened. 30 patients accounting for 42 IS were included in the analysis. Adverse events (AEs) during IS were used as core outcome measures and categorized into neurological and non-neurological AEs. Baseline characteristics, clinical parameters before IS, AEs and functional outcomes were collected using health records. Statistical analysis used generalized linear mixed effects models with LASSO regularization to identify candidate predictors with subsequent bootstrapping to test model stability. As an exploratory analysis, multivariate linear and logistic regression was used to analyze the association between IS and intensive care unit length of stay, duration of mechanical ventilation and functional outcome. Results Mean age was 56.9 (SD 14.8) years and a majority presented with poor-grade SAH (16/30, 53.3%). Neurological and non-neurological AEs occurred in 60.0% (18/30)) of patients. Timing, number of IS attempts, ICP burden, craniectomy status, level of consciousness, heart rate, cerebral perfusion pressure, oxygen saturation, fraction of inspired oxygen and temperature were selected as candidate predictors. Using bootstrapping, timing since disease onset (OR (95% confidence interval, 95% CI), 0.85 (0.75-0.97)), ICP burden (OR (95% CI), 1.24 (1.02-1.52)), craniectomy (OR (95% CI), 0.68 (0.48-0.69)) and oxygen saturation (OR (95% CI), 0.80 (0.72-0.89)) were revealed as relevant biomarkers for neurological AEs, while none of the pre-selected predictors was robustly associated with non-neurological AEs. Conclusions In aSAH, complications during the definite withdrawal of sedation are frequent, but can potentially be predicted using clinical parameters available at the bedside. Prospective multi-center studies are essential to validate these results and further investigate the impact of IS complications.